Pengaruh Green Marketing Terhadap Green Buying Behavior Yang Dimediasi Oleh Environmental Knowledge Dan Green Consumption - Anggraini, Rika (GEMA EKONOMI, 2023)
This study aims to determine the effect of green marketing on green buying behavior mediated by environmental knowledge and green consumption among Starbucks customers in South Jakarta. In collecting data for this study, a sample of Starbucks consumers in South Jakarta was used. The sample used was 140 respondents. The data analysis technique uses Structural Equation Modeling (SEM) with the help of the AMOS computer program. The results of this study indicate that green marketing has a positive effect on green buying behavior which is mediated by environmental knowledge and green consumption of Starbucks customers in South Jakarta, which means that in this study environmental knowledge and green consumption as mediating influence on green marketing and green buying behavior